Konsep Penciptaan Alam Menurut Ibn Rusyd Dan Kaitannya Terhadap Kosmologi (Studi Komparasi Alquran Dan Tripitaka) - Saniatul Hidayah Sania (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2023)
This article aims to find out the continuity between the two concepts of natural creation from two different holy books by using the cosmological approach initiated by Ibn Rushd. The method of presentation in this article is by conducting a library research study, namely references along with scriptures related to the process of creation / occurrence of the universe in the views of the two religions. What is meant by cosmology is the study of the creation of nature that is studied broadly from the point of view of philosophers and the point of view of the Bible. The issue of how the universe came to be is still a matter of endless debate. Ibn Rushd, a Muslim philosopher, contributed his thoughts on the creation of nature. Ibn Rushd's thoughts on cosmology are more or less influenced by the thoughts of Aristotle who initiated the theory of motion.tIbn Rushd tried to lead mankind to knowledge and proof of how the process in the universe is created and the most important thing is the existence and omnipotence of God as the creator. Through this assumption, the concept of the creation of nature from the Koran and the Tripitaka books will be presented, which will be mentioned in each religious text with the previously mentioned approaches.